Different isoforms of growth hormone (20 kD-GH and 22 kD-GH) shows different biological activities in mesenchymal stem cell (MSC). Issue 9 (3rd May 2022) - Zheng, Wei V.; Li, Yaqin; Xu, Yanwei; Lu, Donghui; Zhou, Tao; Li, Dezhi; Cheng, Xianyi; Xiong, Yu; Wang, Shaobin; Chen, Zaizhong
ABSTRACT: There are two main types of growth hormone (GH) in the circulatory system. One is 22 kD-GH, which is the predominant isoform in the circulating system, 90% GH is present as a 22 kD protein, and 10% of GH is present as a 20 kD protein. Amino acid sequences are identical between 20 kD-GH and 22 kD-GH protein, except that 20 kD-GH lacks 15 amino acid residues 32 to 46. Studies have shown that GH has many important biological effects on mesenchymal stem cells (MSCs). However, so far, the cellular characteristics of the two types of GH have not been studied in BM-MSCs. Furthermore, the biological activity of 20 kD-GH has not been explored in BM-MSCs. For this, in the current work, BM-MSCs were used as in vitro cell model. We have carried out the current research using a series of experimental techniques (such as Western-blot and indirect immunofluorescence). Firstly, we explored the cell behavior of two types of GH in the Bm-MSC model and found that they showed different biological characteristics; Secondly, we investigated the biological characteristics of 20 kD-GH and 22 kD-GH, and results showed that 22 kD-GH and 20 kD-GH exhibited different signaling profiles; Thirdly, we found that the 20 kD-GH and 22 kD-GH Gexhibited different regulatory effects on the osteogenic differentiation of BM-MSCs. The current research lays a solid foundation for further studies on the regulatory effects of GH on MSCs.